Characterising the speech phenotype in individuals with craniofacial microsomia: a scoping review protocol. Issue 2 (28th February 2023) - Kinter, Sara; Kotlarek, Katelyn; Meehan, Anna; Heike, Carrie
Abstract : Introduction: Asymmetric mandibular hypoplasia, microtia, tongue and laryngeal anomalies, and soft palate and facial nerve dysfunction are clinical features observed in children with craniofacial microsomia (CFM). Despite involvement of all these structures in hearing and speech, there is limited evidence reporting speech outcomes in this population. Systematic reviews of clinical and surgical interventions related to CFM have been published, but no methodological review of speech outcomes exists. This scoping review will summarise what is known about speech production in individuals with CFM as well as illustrate gaps in the existing body of literature that will guide future research. Methods/analysis: This review will follow the methodological framework for scoping reviews first reported by Arksey & O'Malley and revised by Levac and others. Databases searched will include Ovid MEDLINE, EMBASE, CINAHL, PsycINFO and grey literature. Articles reporting any parameter of speech production in individuals with CFM will be considered for inclusion. Articles published in a language other than English will be excluded. Articles will be screened in three stages: (1) title review, (2) abstract review and (3) full text review. Ten per cent of articles will be rescreened by a second reviewer. Reference lists will be hand reviewed to identify additional relevant articles. Data charting will capture article metadata, study population and design, CFM diagnostic criteria, speech outcome measurement and key findings. The Preferred Reporting Systems for Systematic Reviews and Meta-Analyses Protocols-Extension for Scoping Reviews checklist will guide reporting of results. Descriptive analysis and data visualisation strategies will be used. Ethics and dissemination: Institutional review board approval is not required for a scoping review, as it does not directly involve human subjects. Results will be disseminated through peer-reviewed publication as well as conference presentation.